The Effects of Geopolitical Risks on Oil Price Volatility - Truong, Loc Dong; Doan, Nhien Tuyet; Nguyen, Anh Thi Kim (International Journal of Energy Economics and Policy, 2024)
This study investigates the short-term and long-term effects of geopolitical risks on the volatility of oil price. Data used in this study are the daily geopolitical risk index, oil price and USD index during the period from January 4th, 2010 to December 31st, 2022. Using the autoregressive distributed lag (ARDL) bounds testing approach, the empirical results confirm that the geopolitical risks has positive effects on the volatility of oil price in both the long-term and short-term, meaning that an decrease in the geopolitical risk Index is associated with an increase in the volatility of oil price. In addition, the results derived from the ARDL model indicate that USD index has a positive effect on the volatility of oil price in the short-term, but it has no impact on the volatility of oil price in the long-term. Finally, the results of the error correction model confirm that only 2.81 percent of the disequilibria from the previous trading day is converged and corrected back to the long-run equilibrium in the current trading day.